Ethno-social variants of Spanish in Puno - Godenzzi, Juan Carlos (1987)
An inherent feature of languages ​​is their variation, whether in time, geographical space, social stratum or the circumstance of verbal exchange. The Spanish spoken in Peru in the 16th century is not identical to the one we speak today; the Castilian of Lima and the north coast differs from the Castilian of the highlands or the Amazon jungle. Likewise, the privileged social groups present linguistic features that differentiate them from the impoverished Quechua or Aymara groups.